Manejo de los procesos contables de la Farmacia “Su Receta” de la ciudad de Babahoyo. - Gamarra Morales, Ruddy Camilo (2022)
This is the Farmacy Su Receta, in this way, an effective management of accounting and all its processes often avoids crises that can lead to the closure of the company or organization and that no businessman or entrepreneur wants, there are several clear examples of establishments that have not managed correctly. their accounting processes and the disastrous consequences that these have brought with them. The strategies and methods to manage the accounting processes of a company are many, and they are very useful when applying them, we must take into account that it is necessary to carry out a detailed control of all the processes of the pharmacy such as daily books, ledgers among others but that each one of them is of the utmost importance at the time of keeping accounts. With the realization of this case study, it is expected to obtain good results in the accounting part of the pharmacy through an exhaustive management and control in all its processes, and that there is no longer any type of inconvenience, it is also wanted to achieve that the economy of the pharmacy company improves remarkably, and manages to recover from the losses it had in 2021, which, although they were not many, no manager or entrepreneur wants to lose money.